Kontribusi Self-Esteem dan Self-Determination terhadap Absenteeism pada Mahasiswa Universitas X - Ade Lestari; Yohanes Budiarto; Sandi Kartasasmita (Provitae: Jurnal Psikologi Pendidikan, 2010)
This research aimed an investigating the influence of self-esteem (Rosenberg, 1965) and self-determination (Sheldon & Deci, 1993) toward students’ absemnteeism. Absenteeism is the intention to leave the lecturers. Self-esteem is one’s evaluation about his/hers’ quality they perceive themselves as having. Self-determination is the act or power of making up one’s own mind about what to think or do, without outsife influence or compulsion. The hypothesis was that self-esteem and self-determination influenced the students’ absenteeism. This study involved 280 participants at X University using accidental sampling technique. Using logistic regression, the study showed that self-esteem and self-determination predicted student’ absenteeism for about 1.7%. In other words, self-esteem and self-determination in this study impacted students’ presence in class.Keywords: Absenteeism, self-esteem, self-determinatiomn.